Comparison of carbon ion radiotherapy to photon radiation alone or in combination with temozolomide in patients with high-grade gliomas: Explorative hypothesis-generating retrospective analysis - Combs, Stephanie E.; Bruckner, Thomas; Mizoe, Jun-Etso; Kamada, Tadashi; Tsujii, Hirohiko; Kieser, Meinhard; Debus, Juergen (Radiotherapy and Oncology, 2013)
Purpose To compare retrospectively outcome after photon radiotherapy alone, radiochemotherapy with temozolomide (TMZ), and carbon ion radiotherapy in patients with high-grade gliomas and to generate a hypothetical outcome curve for C12 and TMZ. Patients and methods Patients treated within a Phase I/II Trial with a carbon ion boost were compared retrospectively with randomly chosen patients treated with photons or photons in combination with TMZ in a retrospective analysis. Per treatment group, 16 patients with anaplastic astocytoma (AA), and 32 patients with glioblastoma (GBM) were included. Treatment outcome with focus on progression-free survival (PFS) and overall survival (OS) was analyzed. Results Median OS for patients with GBM was 9 months with RT, 14 months with RCHT group, and 18 months in the C12 group. There was no significant difference between the C12 and the RCHT group. For patients with AA, median OS was 13 months for RT, 39 months for RCHT, and 35 months after C12. The difference from RCHT to C12 was not significant. Median PFS for patients with GBM was 5 months in the RT group, 6 months in the RCHT group, and 8 months in the C12 group. There was a significant difference between the RCHT group and the C12 group. For AA, median PFS was 15 months with RT, 6 months with RCHT, and 34 with C12. Comparing subgroups, C12 was significantly different from RCHT. Based on the significant OS increase from RT to RCHT, and from RT to C12, we projected the potential increase in outcome when combined C12 and TMZ would have been applied. A generated hypothetical curve based on the abovementioned outcome as well as preclinical examinations suggests there might be a benefit from the addition of C12 in patients with high-grade gliomas. Conclusions This exploratory retrospective study suggests a potential benefit of carbon ions in patients with high-grade gliomas. This hypothesis is now being evaluated prospectively in GBM within the randomized CLEOPATRA clinical trial. © 2013 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Carbon ion radiotherapy; Glioblastoma; Outcome; Radiochemotherapy; Temozolomide